2015
DOI: 10.1007/s11661-015-2876-6
|View full text |Cite
|
Sign up to set email alerts
|

Age Hardening in Ultrafine-Grained Al-2 Pct Fe Alloy Processed by High-Pressure Torsion

Abstract: A cast Al-2 wt pct Fe alloy was processed by high-pressure torsion (HPT) at room temperature and then subjected to artificial aging at temperatures of 373 K and 473 K (100°C and 200°C). The aging behavior was studied by Vickers microhardness measurements and by microstructural analyses using transmission electron microscopy and X-ray diffraction. The initial intermetallic structures, composed of a mixture of Al + Al 6 Fe and Al + Al 3 Fe eutectics phases, were partially dissolved in the matrix up to a supersat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
5
11
0
Order By: Relevance
“…4). Similar hardening by annealing has been reported by several authors in some metallic alloys processed by SPD [5,27,29,84,85]. This could be attributed to precipitation of second phase particle, but this is very unlikely in our case, especially in the material processed by N=10 revolutions where original intermetallic particles are still relatively coarse and where the amount of Fe driven in solid solution is very low.…”
Section: Relationship Between Microstructural Features and Microhardnesssupporting
confidence: 90%
See 3 more Smart Citations
“…4). Similar hardening by annealing has been reported by several authors in some metallic alloys processed by SPD [5,27,29,84,85]. This could be attributed to precipitation of second phase particle, but this is very unlikely in our case, especially in the material processed by N=10 revolutions where original intermetallic particles are still relatively coarse and where the amount of Fe driven in solid solution is very low.…”
Section: Relationship Between Microstructural Features and Microhardnesssupporting
confidence: 90%
“…2(a) shows the typical as-cast dendritic structure with pro-eutectic zones in dark (zone A) and Fe-rich eutectic zones in bright (zone B). Similar as-cast structures have been described in previous works [5][6][7]29,[43][44][45][46]. The HAADF STEM image ( Fig. 2(b)) shows similar zones at a higher magnification and clearly exhibits in bright the fine-scaled intermetallic particles within the eutectic areas (labeled B and B').…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…This strengthening results from the combined effect of grain refinement, non‐stable supersaturated solid solution (SSSS) of Fe in Al, and refinement of intermetallic particles during deformation . Recent works have also shown that artificial aging after high‐pressure torsion (HPT) increases both conductivity and tensile strength to the level of 49–51% IACS and above 300 MPa, respectively . Decomposition of supersaturated solid solution, that takes place during aging, leaves the clean aluminum matrix with fine intermetallic particles, which simultaneously enhance alloy conductivity and strength.…”
Section: Introductionmentioning
confidence: 99%